The role of transnational banks in the transmission of global systemic risk - MOMOT, Oleksandr (Scientific journal «World of Finance», 2019)
Introduction. One of the manifestations of financial globalization is the formation and development of cross-border links of transnational banks. This expands opportunities for investment and contributes to the economic development of many countries. At the same time, the increasing complexity of financial ties strengthens the cross-border interdependence of transnational banks, leading to the transfer of financial shocks that arise in some countries to others.The purpose. The article aims to explore the role of multinational banks in the transmission of global systemic risk, identify existing problems supervision of multinational banks as globally systemically important financial institutions and identify solutions.Results. The article deals with the processes of transmission by transnational banks of global systemic risk in the framework of the “theory of infection of financial markets”. The influence of the “general creditor effect” on the spread of crisis phenomena between the economies of different countries is analyzed. The direction of influence of cross-border links of transnational banks on financial stability of the banking system of the country is clarified. Approaches to the identification of globally systemically important banks have been highlighted in accordance with international practice, and tasks have been identified to strengthen regulation and supervision of the activities of transnational banks.Conclusion. Today, regulators have limited ability to prevent the transmission of global systemic risk multinational banks. Many institutional mechanisms exist at national level and aimed at maintaining the financial stability of banking systems and crisis management of banks, there are no globally. However, only coordinated decisions on measures of overcoming the crisis can ensure effective implementation of anti-crisis programs globally